Look! : the ultimate spot-the-difference book - Wilson, April; Wood, A. J., 1960- (New York : Dial Books for Young Readers, 1990)
Paired pictures on each page at first appear identical, but a second look reveals fascinating differences.
School Library Journal
Horn Book Guide
Parents Magazine
K-3
Keywords: Literary recreations -- Juvenile literature; Picture puzzles; Literary recreations; Picture puzzles; Literary recreations